Plant design evaluation on the production of hexane, heptane, liquefied petroleum gases from coconut oil - Yap, Al Jan G. (College of Engineering, 1980)
The plant design presented herein describes a large-scale industrial process of producing petro-chemicals such as Liquefied Petroleum Gas (LPG), solvents, and substitute gasoline mainly from coconut oil. It also provides the reader an idea on the economic feasibility of such a project.